Optimization of Community-Based Marketing Strategies as a Lever for Local MSME Competitiveness through Collaborative Approaches, Digital Engagement, and Socio-Cultural Values - Suherlan; Marjuki (ADMAN: Journal of Contemporary Administration and Management, 2025)
This study aims to analyze the optimization of community-based marketing strategies as a lever for enhancing the competitiveness of local MSMEs, emphasizing the importance of collaborative approaches, the utilization of digital engagement, and the integration of socio-cultural values. The method employed is a literature review with a qualitative and descriptive analysis approach, where data were collected from Google Scholar and credible websites within the period of 1986–2025. Out of a total of 50 articles identified, only 35 were selected through a strict screening process based on relevance and quality. The analysis results show that community-based marketing strategies can strengthen consumer loyalty, expand market reach, and create authentic product differentiation by highlighting local cultural values. Cross-sectoral collaborative approaches have been proven to support MSME capacity building, while digital engagement accelerates interaction and connectivity with consumers. This study asserts that the combination of community, collaboration, digitalization, and culture represents a sustainable strategy relevant to enhancing the competitiveness of MSMEs in Indonesia.